Analysis of Key Factors in Successful Senior High School Principal Leadership - Amirudin, Amirudin; Firdaus, Firdaus; Widodo, Widodo; Saputra, Herman; Ahmad, Raihan Ahma (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
This article examines the factors that contribute to successful principal leadership at SMA Negeri 1 Bunut. Principal leadership is pivotal to the quality of teaching–learning processes and student outcomes; understanding the critical determinants of effective leadership can strengthen secondary-school leadership, particularly in under-researched regional contexts. The study aimed to analyse those critical factors from the principal’s experience and perspectives. A qualitative case-study approach was adopted. Data were collected through in-depth interviews with the principal, supplemented by field observation and document review, and were analysed using thematic analysis and source triangulation. Six overarching themes were identified: motivation to serve in one’s home region; strategies emphasising collaboration, discipline, and collegiality; transformational leadership; direct communication and communication via social media; role modelling as a critical factor; instructional leadership; and a focus on process. Leadership effectiveness was assessed in terms of academic and non-academic achievement, teacher and staff satisfaction, management effectiveness, and achievement of the school’s vision and mission. In sum, successful leadership at SMA Negeri 1 Bunut is underpinned by role modelling, transformational leadership, and attention to both instruction and students’ character development. Other principals and policymakers are encouraged to prioritise role modelling, teacher professional development, instructional leadership, and process-oriented evaluation.